종합병원 사무직원의 직무만족도 - 이성은 (연세대학교 보건대학원, 1985)
[한글] 병원관리의 합리화에 대한 요구가 증대되고 있는 요즈음 병원을 관리운영하는데 주축이 되는 병원 사무직원의 직무만족이 병원관리에 중요한 영향을 미친다고 생각되어 종합병원 사무직원의 일반적 특성 및 직무만족요인과 직무만족도와 상관성을 규명하고저 임의로 선정된 두 개 종합병원 사무직원 157명을 대상으로 연구도구는 Herzberg의 유지-동기부여요인을 토대로 작성한 설문지를 이용하여 1985년 5월 3일부터 5월 10일까지 조사하였다. 백분율, 산술평균, 표준편차, 상관계수, x**2 검정, 분산분석방법을 적용하여 분석한 결과는 다음과 같다. 1. 응답자중 여자가 2/3였고, 연령은 20대가, 학력은 고등학교 졸업이, 근무년수는 5년 미만이 가장 많았다. 2. 직무만족요인과 전체직무만족도와의 상관성은 직무만족 17개 요인중 15개 요인 (적성, 승진가능성, 개인목표와의 일치성, 능력발휘, 상사와의 관계, 동료간의 관계, 자부심, 상사의 감독, 근무처 분위기, 작업조건, 안정성, 전직 의사, 성취감, 권한, 봉급의 적당성)은 통계학적으로 유의한 상관 관계가 있었고 2개 요인 (업무량, 책임)은 통계학적으로 유의한 상관관계가 없었다. 3. 직무만족요인별 평균점수는 대부분의 요인에서 중간점수인 3점을 상회하고 있었고 승진가능성, 개인목표와의 일치성, 전직의사, 봉급의 적당성은 낮은 수준을 나타내었다. 4. 일반적 제특성과 직무만족도와의 관계는 성, 연령, 근무부서, 직위, 근무년수, 월평균급여액은 직무만족도와 통계학적으로 유의한 차이가 있었고 학력과 부양가족의 유무는 통계학적으로 유의한 차이가 없었다. 5. 직무만족요인과 전체직무만족도의 구체적 상관성에서는 앞의 2에서 통계학적으로 상관관계가 있다고 판명된 15요인 중 동료간의 관계를 제외한 14요인이 상관성이 있었는데, 적성, 상사와의 관계, 근무처 분위기는 긍정적일수록 직무만족도가 높아지고 부정적일수 록 직무만족도가 낮아지는 관계가 있었으나 그 외의 요인은 부정적일수록 직무만족도가 낮아졌다. 6. 입직동기는 현 기관에 대한 지역사회의 높은 평가때문이 가장 많았고 현재 가장 원하고 있는 사항은 임금인상이 가장 많았다. [영문] During the past two decades, management of the hospital has been emphasized the rationalization. It has been suggested that the job satisfaction of hospital clerical staff, who might play an important role for management of hospital, influences hospital management. The purpose of this study is to identify the correlation between the job satisfaction factors and the job satisfaction of hospital clerical staff. The survey was based on the questionnairs of 157 clerical staff in two general hospitals. The survey questionnairs were based on Herzberg's maintenance-motivation factors theory. The period for the data was during 8 days, May 3 through May 10, 1985. The data were analyzed by percentage, arythmatic mean, standard deviation, correlation coefficient, chi square and analysis of variance. The results were as a follows: 1. In general characteristics, major distributions showed as follows: Women were 2/3, age was twenties, education level was high school graduates and work period was less than 5 years. 2. The correlation between the job satisfaction factors and the job satisfaction level : There were statistically significant correlations between the fifteen factors out of seventeen factors (aptitude, possibility of promotion, coincidence with senior, relation with colleague, self-confidence, supervision of senior, climate of work place, working conditions, job security, mind toward change of occupation, recognition for accomplishment, authority, suitability of salary) and the job satisfaction. There were not significant correlations between work load, job responsibility and job satisfaction level. 3. The distribution of the mean point of each job satisfaction factors showed low level in the promotion, coincidence with individual goal, mind toward change of occupation and suitability of salary and the other facrors showed bove average level. 4. The significant difference between general characteristics and job satisfactions showed statistically significant difference in the sex, age, work department, work period, salary and existence and nonexistence of dependent family, education level were not significant difference. 5. The trend between the job satisfaction factors and job satisfaction level showed statistically significant correlation the 14 factors. The more aptitude, relation with senior and climate of work place were positive, the more job satisfaction level was high and the more negative, the more low. The more the other factors were negative, the more job satisfaction level was low. 6. The motives of employment showed deu to the high esteem of the hospital in view of the in majority. The one most desire was the salary increase.
보건학과/석사